Inclusive Campus Design in Islamic Institution - Arif Budi Sholihah (Journal of Architectural Research and Design Studies, 2024)
Designing an inclusive campus is an evolving process. Each educational institution has varying levels of awareness of the importance of inclusive campus design. As the highest public educational institution that follow Islamic values, Islamic University has a strategic function to serve as a benchmark for providing more inclusive facilities. This study will explore the process and challenges to implement inclusive design in its buildings in Universitas Islam Indonesia (UII) Yogyakarta. To understand how inclusive design has been implemented in the UII Main Campus facilities, qualitative methodologies were employed, including field observations, access audits, and interviews with key stakeholders. The results indicate that awareness of the implementation of inclusive design at the UII Main Campus develops gradually alongside the availability of universal technical accessibility and design standards and the growth of an understanding of their significance. The finding shows that the younger the generation of buildings, the more inclusive the designs. Keywords: inclusive design; Islamic values; Islamic institution